ESG Performance and Its Role in Mitigating Stock Price Crash Risk: Evidence from Indonesian Listed Companies - Isnaini Nuzula Agustin; Julia Ananda Caesaria; Hery Haryanto (Manunggal Halim Jaya, 2026)
This study examines the extent to which ESG performance influences stock price crash risk (SPCR) among companies listed on the Indonesia Stock Exchange (IDX). Using ESG Score data from the Refinitiv database, this study analyzes 232 firm-year observations from 2018 to 2023. SPCR is measured using Negative Skewness (NSKEWNESS), an indicator capturing the asymmetry of return distributions that reflects the buildup of hidden bad news and Down-to-Up Volatility (DUVOL), which captures downside volatility relative to upside movements. Regression results show that the aggregate ESG Score significantly reduces SPCR when measured with NSKEWNESS, indicating that firms with stronger ESG engagement are less likely to experience extreme negative price declines. When decomposed, the Environmental and Social components significantly mitigate SPCR, while Governance exhibits a negative but insignificant effect. However, none of the ESG components significantly influence DUVOL, suggesting that ESG practices may be more effective in addressing long-term crash risk rather than short-term price volatility. These findings highlight the role of ESG in promoting market resilience and underscore the importance of transparent and comprehensive sustainability reporting for corporate managers, investors, and regulators.